Valves of the small coronary veins in porcine hearts - Musil, Vladimír; Sach, Josef; Patzelt, Matej; Kachlik, David; Stingl, Josef (Journal of morphology, 2019)
The aim of the study was to investigate the existence of valves in small peripheral coronary veins of porcine hearts. The study was performed on 20 porcine hearts using standard histological methods. The veins in the subepicardial and intramyocardial regions of the anterior and posterior parts of the interventricular septum and in the wall of the right atrium were studied. Valves were present in intramyocardial veins (diameter of 75-180 μm), in the veins located just beneath the external surface of the myocardium (diameter 120-170 μm) and in the terminal segments of the ventricular veins (diameter 250 μm) opening into the stems of the anterior interventricular vein and middle cardiac vein. Valves were also recorded in most veins of the subepicardial space. The described rich presence of valves in the small coronary veins may contribute to a better comprehension of their hemodynamic properties. These findings may also help to improve the understanding of the efficacy of retrograde application of medications, a novel technique in cardiology and cardiac surgery.
Keywords: srdeční síně; koronární cévy; Heart Atria; Heart Valves; Swine; Coronary Vessels; Animals; Male; Myocardium; myokard; prasata; zvířata; Female; mužské pohlaví; ženské pohlaví; srdeční chlopně